2015
DOI: 10.1038/nature16462
|View full text |Cite
|
Sign up to set email alerts
|

Competition between DNA methylation and transcription factors determines binding of NRF1

Abstract: Eukaryotic transcription factors (TFs) are key determinants of gene activity, yet they bind only a fraction of their corresponding DNA sequence motifs in any given cell type. Chromatin has the potential to restrict accessibility of binding sites; however, in which context chromatin states are instructive for TF binding remains mainly unknown. To explore the contribution of DNA methylation to constrained TF binding, we mapped DNase-I-hypersensitive sites in murine stem cells in the presence and absence of DNA m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

38
395
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 422 publications
(434 citation statements)
references
References 54 publications
38
395
0
1
Order By: Relevance
“…We examined several primary sequence properties of genomic DNA known to impact in vivo binding, including motif clusters (Pott and Lieb, 2015) and TF sensitivity to DNA methylation in motifs (Domcke et al, 2015), by restricting predictions to peaks containing a single motif with no strong motifs within 100 bp, or to peaks containing motifs with no methylcytosine ( Figure S4A). We observed improved performance of motif inference relative to DAP signal for ABI5, but not for ANAC055, suggesting these two TFs have different binding environment requirements and DAP-seq signal may achieve better predictive power by directly capturing environment features other than core recognition sequence.…”
Section: Dap-seq Captures Tf Binding Sites Identified By Chip-seqmentioning
confidence: 99%
“…We examined several primary sequence properties of genomic DNA known to impact in vivo binding, including motif clusters (Pott and Lieb, 2015) and TF sensitivity to DNA methylation in motifs (Domcke et al, 2015), by restricting predictions to peaks containing a single motif with no strong motifs within 100 bp, or to peaks containing motifs with no methylcytosine ( Figure S4A). We observed improved performance of motif inference relative to DAP signal for ABI5, but not for ANAC055, suggesting these two TFs have different binding environment requirements and DAP-seq signal may achieve better predictive power by directly capturing environment features other than core recognition sequence.…”
Section: Dap-seq Captures Tf Binding Sites Identified By Chip-seqmentioning
confidence: 99%
“…Alternative methods are needed for capturing genome-wide binding data for many organisms. In vitro TFBS identification methods such as Protein Binding Microarrays (PBM) and High Throughput Systematic Evolution of Ligands by Exponential Enrichment (HT-SELEX) have achieved the highest throughput for deducing TF binding specificities in vitro [9][10][11] , but these methods use short synthetic oligonucleotides lacking secondary DNA modifications and genomic context, both important determinants of selective TF binding in vivo [12][13][14][15][16] . The DAP-seq technique 15 described here employs an in vitro-expressed affinitytagged TF in combination with high-throughput sequencing of a genomic DNA library, allowing for the generation of genome-wide binding site maps reflective of both local sequence context and DNA methylation status.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, Rollins et al reported that Alu repeats are largely excluded from unmethylated domains, but tend to occupy the boundaries of these domains (Rollins et al 2006;Edwards et al 2010). The presence of variably methylated Alu elements near promoters might indicate boundary plasticity ensuing changes in chromatin accessibility and transcription factor binding regulation (Domcke et al 2015;Elliott et al 2015;Maurano et al 2015;Schübeler 2015). In this regard, it has been shown that most DNA methylation changes associated with development and cancer do not occur in CpG islands, but rather in sequences up to 2-kb away, which were termed CpG island shores (Doi et al 2009;Irizarry et al 2009).…”
Section: Alu-related Determinants Of Global Genomic Hypomethylation Amentioning
confidence: 99%
“…Moreover, a minority of Alu elements display signs of intrinsic functionality including the presence of activating histone modifications and a DNA unmethylated state (Rodriguez et al 2008b;Saito et al 2009;Edwards et al 2010;Yoshida et al 2011;Ward et al 2013;Xie et al 2013;Su et al 2014). The presence of diverse transcription factor binding motifs in Alu sequences is common (Ruiz-Narváez and Campos 2008;Cui et al 2011;Deininger 2011), but motif occupancy appears to be constrained by DNA methylation (Wang et al 2012;Medvedeva et al 2014;Domcke et al 2015;Maurano et al 2015;Schübeler 2015). Hence, hypomethylation of Alu repeats might enable the binding of transcription and epigenetic factors affecting gene activity and genomic architecture in both normal and cancer cells.…”
Section: Individual Features Of Unmethylated Alu Repeats and Functionmentioning
confidence: 99%